A Qualitative Study: An Evaluation of Smoking Among Young People Aged 15–20 Years in Turkey Using Bourdieu’s Concepts - Sankır, Şebnem; Sankır, Hasan; Çakır Kardeş, Vildan; Atasoy, Nuray (Addicta: The Turkish Journal on Addictions, 2022)
Smoking is becoming increasingly common among Turkish young people aged between 15 and 20 years despite the preventive measures taken to control this increase. The current study aimed to demonstrate the sociocultural meaning attributed to smoking behaviors. For this purpose, semistructured in-depth interviews with 27 smokers aged under 20 years and with one of their parents were conducted. Bourdieu’s concepts were adopted to comprehend and thus get an overall perspective of the smoking practices among youth and sociocultural factors underlying cigarette use. In this study, participants had a smoking behavior that first emerged within the family and then was witnessed among the same-age peers and was found to influence the youngsters’ perceptual categories and cognition structures regarding cigarettes. In addition, youngsters develop smoking behaviors to preserve their social capital and to gain social acceptance among their peers who have extensive cigarette use. They also use cigarette to get symbolic benefits, such as building a cool image. The conclusions of this study help us in understanding the relationship between smoking and lives, context, economic and cultural resources, and consumption practices within the family.